Spanish grammar in context - Kattan-Ibarra, Juan; Howkins, Angela (London Routledge, 2014)
"Spanish Grammar in Context provides an accessible and stimulating approach to learning grammar. Authentic texts are used to illustrate and explain the key areas of Spanish grammar, followed by a range of exercises to help students reinforce and test their understanding. An answer key is also presented at the back of the book. Features include: - A rich variety of texts sourced from all over the Spanish-speaking world, including excerpts from contemporary literature, magazines and newspapers - Texts carefully selected to cover topical issues and themes relevant to contemporary Spain and Latin America - Clear, user-friendly and comprehensive coverage of grammar, aided by a list of grammatical terms - An abundance of exercises designed to thoroughly build up grammatical understanding and effective comprehension and communication skills - Free companion website featuring an assortment of extra exercises for additional practice This third edition has been revised and updated throughout and offers new exercises and fresh texts. Spanish Grammar in Context will be an essential resource for intermediate to advanced students of Spanish. It is suitable for both classroom use and independent study"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Spanish language -- Grammar; Spanish language -- Grammar -- Problems, exercises, etc; Spanish language -- Textbooks for foreign speakers -- English